High-Affinity Binding of Metallacarborane Cobalt Bis(dicarbollide) Anions to Cyclodextrins and Application to Membrane Translocation - Assaf, Khaleel I; Begaj, Barbara; Frank, Angelina; Nilam, Mohamed; Mougharbel, Ali S; Kortz, Ulrich; Nekvinda, Jan; Grüner, Bohumír; Gabel, Detlef; Nau, Werner M (The Journal of organic chemistry, 2019)
Metallacarboranes are a class of inorganic boron clusters that have recently been recognized as biologically active compounds. Herein, we report on the host-guest complexation of several cobalt bis(1,2-dicarbollide) anions (COSANs) with cyclodextrins (CDs) in aqueous solution. The binding affinities reach micromolar values, which are among the highest known values for native CDs, and exceed those for neutral hydrophobic organic guest molecules. The entrapment of the COSANs inside the cavity of CDs was confirmed using NMR and UV-visible spectroscopy, mass spectrometry, cyclic voltammetry, and isothermal titration calorimetry. Complexation by CDs greatly influences the photophysical and electrochemical properties of COSANs. In combination with indicator displacement assays, a label-free fluorescence-based method was developed to allow real-time monitoring of the translocation of COSANs through lipid bilayer membranes.
Keywords: cyklodextriny; kobalt; molekulární modely; Cyclodextrins; Anions; anionty; liposomy; Lipid Bilayers; Models, Molecular; termodynamika; Cobalt; Thermodynamics; lipidové dvojvrstvy; sloučeniny boru; Boron Compounds; Liposomes; Organometallic Compounds; organokovové sloučeniny